Treasures from Trash: Review of Kelsi Nagy and Philip David Jonson II, eds. Trash Animals: How We Live with Nature’s Filthy, Feral, Invasive, and Unwanted Species - Weiss, Andrew (Humanimalia, 2014)
Kelsi Nagy and Philip David Jonson II, eds. Trash Animals: How We Live with Nature’s Filthy, Feral, Invasive, and Unwanted Species. Minneapolis: University of Minnesota Press. Xvi + 314 pp. $24.95. Pbk.